Analisis Performance Website Bima Kemendikbud Terhadap Kepuasan Pengguna Menggunakan Metode System Usability Scale: measuring the performance of the bima website on user satisfaction - muhammad amirudin (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Bima is an acronym for Research and Community Service Information Base. So that currently there has never been an evaluation of the performance of the website. Making it easy to find out which information sites are intended for from this research is a measurement of the usefulness of the website for sending proposals, reporting on the progress of activities, and online-based research results. The purpose of the study was to obtain user satisfaction and to obtain results from a questionnaire that affected the performance of the Ministry of Education and Culture's bima website. Measure the performance of the Ministry of Education and Culture's bima website by analyzing website performance, interaction and website users on user satisfaction. Analysis of the performance of this website is carried out through several stages, namely data collection with user satisfaction results. Then analyze the System Usability Scale method site by preparing a questionnaire based on the dimensions of the System Usability Scale to support the research. The research conducted observations, literature studies and surveys as the most influential data collection in building website performance satisfaction for the Ministry of Education and Culture's bima users is the information provided. Keywords: Website performance, System Usability Scale, user satisfaction, Bima Kemendikbud